Activité du manager de réception à l’épreuve de la digitalisation : cas d’un projet d’accueil en mobilité dans une chaîne hôtelière internationale - Pierre Flandrin (Association Recherche et Pratique sur les Activités, 2021)
The article explores the activity of the front office manager (FOM) in the context of the digitalization in three hotels of an international hotel chain. The methodology allowed us to analyze the FOM’s activity on two levels: his activity as part of his daily management duties in a digitized environment and his activity in the accompaniment of a pilot reception digitalization project via smartphone. The ergonomic analysis indicates a controversial effect of technologies with the reinforcement of the managerial framework and of control of the managerial activity. The ergonomic analysis also reveals the regulatory role of the FOM. In the context of a change in the reception mode, the results reveal attempts to ‘empower’ the FOM to make the smartphone acceptable to the receptionists through situations designed to develop the receptionists’ emotional work. This managerial framework does not allow the FOM to be in a position to take steps to develop real power for the receptionists to act with the device. Certain suggestions are made to consider digitalization as a source of activity development. One of these is based on bringing designers and users (managers, receptionists and revenue managers) together around the objective of personalizing the service. Another approach is to think about the future organization of work with technology upstream of the design phase, through the creation of dynamic simulations that take into account the real activity at the reception desk.